Geometric size effect on IMC growth and elements diffusion in Cu/Sn/Cu solder joints. Issue 2 (3rd April 2017) - Zhu, Yan; Sun, Fenglian
Abstract : Purpose: The purpose of this paper is to investigate the effect of geometric size on intermetallic compound (IMC) growth and elements diffusion of Cu/Sn/Cu solder joint and establish the correlation model between the thickness of the IMC layer and size of the solder joint on the dozens of microns scale. Design/methodology/approach: The sandwich-structured Cu/Sn/Cu solder joints with different gaps between two copper-clad plates (δ) are fabricated using a reflow process. The microstructure and composition of solder joints are observed and analyzed by scanning electron microscopy. Findings: After reflow, the thickness of the IMC and Cu concentration in solder layers increase with the reduction of δ from 50, 40, 30, 20 to 10 μm. During isothermal aging, the thickness of the IMC fails to increase according to the traditional parabolic rule due to changes in Cu concentration. The reduction of δ is the root cause of changes in Cu concentration and the growth rule of the IMC layer. A correlation model between the thickness of the IMC layer and δ is established. It is found that the thickness of the IMC layer is the function of aging time and δ. With δ reducing, the main control element of IMC growth transfers from Cu to Sn. Originality/value: This paper shows the changes of IMC thickness and elements concentration with the reduction of the size of solder joints on the dozens of microns scale. A correlation model is established to calculate the thickness of the IMC layer during aging.